From eco-urbanism to eco-fusion: an augmented multi-scalar framework in sustainable urbanism - Cheshmehzangi, Ali; Flynn, Andrew; Tan-Mullins, May; Xie, Linjun; Deng, Wu; Mangi, Eugenio; Chen, Weixuan (2021)
This paper introduces the new concept of “eco-fusion” through an exploratory case study project. It suggests the importance of multi-scalar practice in the broader field of eco-urbanism. This study introduces eco-fusion as a multiplexed paradigm, which is then discussed in two different development models. This paper first highlights the position of “eco” in urbanism by providing a brief account of key terms and how they relate to one another. It then points out the associations between eco-fusion and sustainable urban development. Through an exploratory case study example in China, the practical factors of eco-development are assessed. The study aims to provide a set of intermediate development stages while maintaining each spatial level’s interface in their own defined and distinguished contexts. The key objective is to consider integrating the natural and built environments, which is considered the best practice of eco-development in urbanism. This study’s findings highlight integrated methods in eco-urbanism and suggest new directions for eco-planning/eco-design strategies.